MicroRNA-21 Limits Uptake of Listeria monocytogenes by Macrophages to Reduce the Intracellular Niche and Control Infection - Johnston, Daniel G. W.; Kearney, Jay; Zasłona, Zbigniew; Williams, Michelle A.; O'Neill, Luke A. J.; Corr, Sinéad C. (Frontiers in Cellular and Infection Microbiology, 2017)
MiRNAs are important post-transcriptional regulators of gene expression. MiRNA expression is a crucial part of host responses to bacterial infection, however there is limited knowledge of their impact on the outcome of infections. We investigated the influence of miR-21 on macrophage responses during infection with Listeria monocytogenes, which establishes an intracellular niche within macrophages. MiR-21 is induced following infection of bone marrow-derived macrophages (BMDMs) with Listeria. MiR-21-/- macrophages display an increased bacterial burden with Listeria at 30 mins and 2h post-infection. This phenotype was reversed by the addition of synthetic miR-21 mimics to the system. To assess the immune response of wildtype (WT) and miR-21-/- macrophages, BMDMs were treated with bacterial LPS or infected with Listeria. There was no difference in IL-10 and IL-6 between WT and miR-21-/- BMDMs in response to LPS or Listeria. TNF- was increased in miR-21-/- BMDMs stimulated with LPS or Listeria compared to WT macrophages. We next assessed the production of nitric oxide (NO), a key bactericidal factor in Listeria infection. There was no significant difference in NO production between WT and miR-21-/- cells, indicating that the increased bacterial burden may not be due to impaired killing. As the increased bacterial load was observed early following infection (30 mins), we questioned whether this is due to differences in uptake of Listeria by WT and miR-21-/- macrophages. We show that miR-21-deficiency enhances uptake of FITC-dextran and FITC-Escherichia coli bioparticles by macrophages. The previously observed Listeria burden phenotype was ablated by pre-treatment of cells with the actin polymerization inhibitor cytochalasin-D. From analysis of miR-21 targets, we selected the pro-phagocytic regulators myristoylated alanine-rich C-kinase substrate (MARCKS) and Ras homolog gene family, member B (RhoB) for further investigation. MARCKS and RhoB are increased in miR-21-/- BMDMs, correlating with increased uptake of Listeria. Finally, intra-peritoneal infection of mice with Listeria led to increased bacterial burden in livers of miR-21-/- mice compared to WT mice. These findings suggest a possible role for miR-21 in regulation of phagocytosis during infection, potentially by repression of MARCKS and RhoB, thus serving to limit the availability of the intracellular niche of pathogens like L. monocytogenes.